Plastic pollution in the Labrador Sea: An assessment using the seabird northern fulmar Fulmarus glacialis as a biological monitoring species - Avery-Gomm, Stephanie; Provencher, Jennifer F.; Liboiron, Max; Poon, Florence E.; Smith, Paul A. (Marine Pollution Bulletin, 2017)
Plastic is now one among one of the most pervasive pollutants on the planet, and ocean circulation models predict that the Arctic will become another accumulation zone. As solutions to address marine plastic emerge, is essential that baselines are available to monitor progress towards targets. The northern fulmar (Fulmarus glacialis), a widely-distributed seabird species, has been used as a biological monitor for plastic pollution in the North Sea, and could be a useful monitoring species elsewhere. We quantified plastic ingested by northern fulmars from the southeastern Canadian waters of the Labrador Sea with the objective of establishing a standardized baseline for future comparisons. Over two years we sampled 70 fulmars and found that 79% had ingested plastic, with an average of 11.6 pieces or 0.151g per bird. Overall, 34% of all fulmars exceeded the Ecological Quality Objective for marine litter, having ingested >0.1g of plastic.